IMPLEMENTASI MANAGEMENT BOARDING DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SMP ISLAM AL-AZAMI CIANJUR - D. Siska Amaliyah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
IMPLEMENTATION OF MANAGEMENT BOARDING IN FORMING CHARACTERS OF STUDENTS AT AL-AZAMI ISLAMIC JUNIOR HIGH SCHOOL, CIANJURThis research aims to find out how the implementation of Boarding management in shaping Islamic character in Al-Azami Islamic Intermediate Fullday and Boarding School Cianjur. The research method was field research with qualitative research. Data collection techniques are done by observation, in-depth interviews, and documentation. Testing the validity of the data using source triagulation techniques. The results of this research indicate that by looking at the concept of Boarding management in shaping Islamic character in the Al-Azami Islamic Intermediate Fullday and Boarding School Cianjur has a significant impact on the objectives of Islamic character education in students personalities by instilling a sense of love and family that is instilled by the leadership to all educators and students, so its build the right  attitude of responsibility, obedience, and a sense of family from students in Al-Azami Islamic Intermediate Fullday and Boarding School Cianjur, they never have a bad note as a naughty students that usually done among general teenagers, which of course creates anxiety and anxiety among parents, school, and community. From this attitude they succeeded in gaining a number of academic achievements at the Al-Azami Islamic Intermediate Fullday and Boarding School Cianjur students at the sub-district, district, and provincial even level.